MICROSPONGES AS A NEOTERIC CORNUCOPIA FOR DRUG DELIVERY SYSTEMS - RAJESWARI, SARIPILLI; SWAPNA, VANAPALLI (International Journal of Current Pharmaceutical Research, 2019)
Microsponges (MSPs) are at the forefront of the rapidly developing field of novel drug delivery systems which are gaining popularity due to their use for controlled release and targeted drug delivery. The microsponge delivery system (MDS) is a patented polymeric system consisting of porous microspheres typically 10-25 microns in diameter, loaded with an active agent. They are tiny sponge-like spherical particles that consist of a myriad of interconnecting voids within a non-collapsible structure with a large porous surface through which active ingredient is released in a controlled manner. Microsponge also hold a certification as one of the potential approaches for gastric retention where many oral dosage forms face several physiological restrictions due to non-uniform absorption pattern, inadequate medication release and shorter residence time in the stomach. This type of drug delivery system which is non-irritating, non-allergic, non-toxic, can suspend or entrap a wide variety of substances, and can then be incorporated into a formulated product such as gel, cream, liquid or powder that is why it is called as a “versatile drug delivery system”. It overcomes the drawbacks of other formulations such as frequency of dosing, drug reaction, incompatibility with environmental condition. These porous microspheres were exclusively designed for chronotherapeutic topical drug delivery but attempt to utilize them for oral, pulmonary and parenteral drug delivery were also made. The present review elaborates about the multifunctional microsponge technology including its preparation, characterization, evaluation methods along with recent research and future potential.